An exploratory study on the legitimacy of energy megaproject in South Africa - Moloi, Peter Mokholwane (My University, 2018)
South Africa was hit with a lot of power cuts in the late 2000s as a result of an ageing and underfunded infrastructure. The current government had other priorities which included electrification of the whole communities overlooked by the pre-1994 government. This emphasis meant that investment in power generation was neglected resulting in an infrastructure that was not coping. The study explored the legitimacy of opting for energy megaprojects as viable option to ease the pressure. It appears as if the approach to massive power generation investment is a trend started in 1923, when the power utility, Electricity Supply Commission Company was established. The motivation behind South Africa’s proclivity towards energy megaprojects is pitted against the impact of these projects to the end users in relation to cost and benefit. A cross-sectional case study approach focusing on multiple cases, which are: Medupi Power Station; Ingula Power Station; and the Sere Energy Farm were adopted in a quest to meet the objectives of the study. The mixed method approach to data collection and analysis has been adopted to realize the research objectives and resolve the research question. Key data collection instruments included surveys directed at the end users of electricity, questionnaires and semi-structured interviews directed at professionals within the energy sector, questionnaires directed at organisations representing workers within the energy sector. The study found that the energy megaprojects are fundamentally not legitimate projects to resolving power generation and supply challenges in South Africa. The study further found amongst others that the energy megaprojects have negative financial impact to end users and consumers of electricity. This is contrary to one of the key objectives of the Integrated Energy Plan promulgated by the Department of Energy. The study recommends that reasonably scaled, manageable and responsive energy projects be investigated and possibly adopted to ensuring cost efficiency on energy generation and supply while meeting the key objectives of the Integrated Energy Plan.
Keywords: Project management; Construction projects--Environmental aspects; Construction projects